First, I want to ask this question. Would r+r+r+r+r equal 5r?
Ok, now onto the simplifications that I'm having trouble with:
1. f - 3f + 2 - f +1
2. -8q + 6 + 5q - 3
3. h + 5h - 3 - 6h
4. 2a- 5(a +1)
I have no clue what I'm doing here.
First, I want to ask this question. Would r+r+r+r+r equal 5r?
Ok, now onto the simplifications that I'm having trouble with:
1. f - 3f + 2 - f +1
2. -8q + 6 + 5q - 3
3. h + 5h - 3 - 6h
4. 2a- 5(a +1)
I have no clue what I'm doing here.
Sorry, here are my steps:
1. f - 3f + 2 - f +1
= f - (f + f + f) + 2 - f + 1
= f + f + 2 - f + 1
= f + (f - f) + 2 + 1
= f + 2 + 1
= f + 3
2. -8q + 6 + 5q - 3
= (-8q + 5q) + 6 - 3
= -3q + 6 - 3
= -3q + 3
3. h + 5h - 3 - 6h
= 6h - 3 - 6h
= (6h - 6h) - 3
= - 3
4. 2a- 5(a +1)
= 2a - 5a +1
= -3a +1
I guess it's a good thing I redid it showing my steps; #3 and 4 were wrong.